Numerical Investigation on Surface Coverage of Weakly-Adsorbed Molecular SO2 Contaminant in a PEM Fuel Cell Cathode - Hasmady, Saiful; Fushinobu, Kazuyoshi (International Journal of Engineering and Technology, 2018)
This paper describes attempt to numerically predict surface coverage of SO2 contaminant in a PEMFC cathode, as a step towards assessing its impact towards cell performance. Three-dimensional macro-homogeneous conservation equations of two-phase fluid flow is coupled with micro-scale cathode ORR kinetics to solve for surface coverage distribution of O-ad and SO2-ad at the surface of the catalyst layer for bulk SO2 concentrations of 2.5 and 5.0 ppm. At 2.5 ppm, SO2-ad is predicted to block ca. 20% of the active sites at cell current density of 0.2 A/cm2. The effect of SO2-ad blockage is then correlated with loss in cell performance. The numerical results are compared with experimental data from literature, which confirms that though the model successfully predicted higher potential loss with higher bulk SO2 concentration in the reactant feed, inclusion of only weakly-adsorbed SO2 will under-predict the exact potential loss experienced by the cell. This means strongly adsorbed sulfur containing species must be adopted into the model in order to better predict the severity of degradation of the cell due to SO2 contamination.